Environmental Consequences Of the Capital Relocation In the Republic Of Kazakhstan - Natalia A. Koldobskaya (Geography, Environment, Sustainability)
The large-scale socio-economic and political changes that have taken place in the post-Soviet space since the early 1990s have led to cardinal transformations of the economy and settlement in the former Soviet republics. The purpose of the study is to identify patterns and main features of the transformation of the environmental situation in the old and new capitals of the Republic of Kazakhstan. The subject of this article is the ecological transformation in former and modern capitals of the Republic of Kazakhstan, which was affected not only by post-Soviet changes but also by the transfer of capital functions from Almaty to Nur-Sultan. For a comprehensive analysis of the situation, the state of atmospheric air, water, soil and green spaces were considered. Quantitative calculations and qualitative assessment of the ecological situation showed that the environmental situation of both cities in 2020 was very similar, but the environmental state transformation index does not reach the level of Almaty due to the higher self-cleaning potential of the city and a newer and, accordingly, more environmentally friendly traffic flow. In two cities over the past 20 years, we registered a negative trend in impact level on water sources: a decrease in water consumption in Almaty by 45%, in Nur-Sultan by 27% since 2000. Modernization of plumbing and sewerage systems can reduce water leaks and improve wastewater transport to wastewater treatment plants. In 1998–2020, the environmental situation in Nur-Sultan changed much faster than in Almaty due to the low base effect and the transfer of capital functions because of the emissions from motor transport. However, for Almaty and Nur-Sultan, it can be concluded that the environmental situation by 2020 had been deteriorating much faster than it improved after the collapse of the USSR.